2020
DOI: 10.1177/0890117120931710
|View full text |Cite
|
Sign up to set email alerts
|

Health Communication and the Arts in the United States: A Scoping Review

Abstract: Objectives: Guided by the hypothesis that the arts can play a role in changing attitudes, beliefs, and health behaviors, the objectives of the study were to (1) overview artistic practices, interventions, and research being conducted at the intersection of the arts and health communication and (2) identify desired and observed outcomes and variables measured in these studies. Data Source: The search strategy was developed iteratively with 2 health science librarians and conducted using 8 databases (Applied Soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
2
15
0
1
Order By: Relevance
“…It was conducted as one of two scoping reviews that were part of a larger project focusing on the use of the arts in community health settings in the United States. The first scoping review examined arts-based programs in health communication ( Sonke et al, 2021b ). A protocol for the entire project, inclusive of both reviews, was registered with the JBI in January 2019, under the preliminary title “Engaging the Arts in Health Communication and Wellbeing: A Scoping Review.”…”
Section: Methodsmentioning
confidence: 99%
“…It was conducted as one of two scoping reviews that were part of a larger project focusing on the use of the arts in community health settings in the United States. The first scoping review examined arts-based programs in health communication ( Sonke et al, 2021b ). A protocol for the entire project, inclusive of both reviews, was registered with the JBI in January 2019, under the preliminary title “Engaging the Arts in Health Communication and Wellbeing: A Scoping Review.”…”
Section: Methodsmentioning
confidence: 99%
“…There is growing recognition of the role played by different art forms in improving health and well-being (Clift and Camic, 2016 ; Fancourt and Finn, 2019 ; Nitzan and Orkibi, 2020 ; Sonke et al, 2021 ), whether as part of everyday life (not for health purposes but with a secondary health benefit), within arts programs designed to promote health, or within specific therapeutic interventions provided by qualified creative arts therapists in various kinds of healthcare settings. The creative arts therapies (CATs) are characterized by the clinical and evidence-informed use of the arts within a therapeutic relationship that relies on experiential and action-based interventions (De Witte et al, 2020c ).…”
Section: Introductionmentioning
confidence: 99%
“…six film studies out of the 78 that met inclusion criteria. 15 The review focused on outcomes research and descriptive studies, the use of arts in nonclinical settings in the United States, arts interventions that influence health or health-related experiences, and outcome measures such as knowledge, awareness, beliefs, risk perceptions and cultural acceptance. Other arts forms studied included photography, theatre and dance, and digital arts.…”
Section: Identify Culturally Relevant Media To Propagate Covid-19 Songs and Dramamentioning
confidence: 99%
“…Lessons from such studies may be useful to generate the evidence regarding the use of songs and drama for addressing the current and future pandemics. A recent review of arts‐based health communication in the United States identified only three music/song and six film studies out of the 78 that met inclusion criteria 15 . The review focused on outcomes research and descriptive studies, the use of arts in nonclinical settings in the United States, arts interventions that influence health or health‐related experiences, and outcome measures such as knowledge, awareness, beliefs, risk perceptions and cultural acceptance.…”
Section: Test the Effectiveness Of Arts Approachesmentioning
confidence: 99%